Use of Next-Generation Sequencing for the Molecular Diagnosis of 1,102 Patients With a Autosomal Optic Neuropathy - Charif, Majida; Bris, Céline; Goudenège, David; Desquiret-Dumas, Valérie; Colin, Estelle; Ziegler, Alban; Procaccio, Vincent; Reynier, Pascal; Bonneau, Dominique; Lenaers, Guy; Amati-Bonneau, Patrizia (Frontiers in Neurology, 2021)
Advances in next generation sequencing (NGS) facilitate the diagnosis of genetic disorders. To evaluate its use for the molecular diagnosis of inherited optic neuropathy (ION), a blinding disease caused by the degeneration of retinal ganglion cells, we performed genetic analysis using targeted NGS of 22 already known and candidate genes in a cohort of 1,102 affected individuals. The panel design, library preparation, and sequencing reactions were performed using the Ion AmpliSeq technology. Pathogenic variants were detected in 16 genes in 245 patients (22%), including 186 (17%) and 59 (5%) dominant and recessive cases, respectively. Results confirmed that OPA1 variants are responsible for the majority of dominant ION, while ACO2 and WFS1 variants are also frequently involved in both dominant and recessive forms of ION. All pathogenic variants were found in genes encoding proteins involved in the mitochondrial function, highlighting the importance of mitochondria in the survival of retinal ganglion cells.